Testing and refining an approach to identifying health and social care needs in probation - Sirdifield, Coral (Probation journal, 2024)
We piloted an approach to identifying the health and social care needs of people on probation using a survey consisting of validated screening tools and key additional questions. We share findings from our analysis of the sample data, showing that there is a high complexity of needs in this population, with 65.4% of participants reporting at least one unmet need. We also explore the acceptability of this approach to identifying needs being used in routine probation practice and make recommendations about how identification and recording of needs could be approached and further researched in the future.